Lithium-ion conductor polymer ceramic membrane

JP7668545B2Active Publication Date: 2025-04-25MONASH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022508870
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-12
Filing Date
2020-08-12
Publication Date
2025-04-25
Estimated Expiration
2040-08-12

AI Technical Summary

Technical Problem

Existing lithium-selective membranes exhibit low lithium selectivity and poor stability, limiting their practical applications in lithium recovery from sources such as brines and lithium-containing solutions.

Method used

A separation membrane comprising a target ion-permeable polymer-ceramic composite material, specifically a lithium target ion porous support substrate with a lithium target ion permeable polymer-ceramic composite material made of Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 (LATP) ceramic bound with polyvinylidene fluoride (PVDF), is developed for selective lithium ion separation.

Benefits of technology

The membrane achieves high lithium selectivity and stability, enabling efficient lithium recovery from various sources, including seawater and brines, with lithium recovery rates up to 98.5% and selectivity ratios of up to 46 for lithium over magnesium and 10 for lithium over sodium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000027_0000
    Figure 00000027_0000
  • Figure 00000028_0000
    Figure 00000028_0000
  • Figure 00000029_0000
    Figure 00000029_0000
Patent Text Reader

Abstract

An ion-permeable membrane for selectively allowing the permeation of target ions, preferably lithium, through the membrane, the membrane comprising a target ion-permeable composite, the composite comprising a target ion-permeable ceramic and at least one organic polymer, the organic polymer bonded to the target ion-permeable ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] Field of Invention The present invention relates to membranes and apparatus for the recovery of lithium ions and for the selective recovery of lithium ions from liquid solutions, particularly aqueous solutions (e.g., brine (or saline)). [Background technology]

[0002] (background) Global demand for lithium is growing. Lithium salts are extracted primarily from both mineral deposits (or mineral precipitates) and salt lakes. Processes (or methods) used to produce lithium (Li) and lithium compounds include acid hydrolysis of minerals and chemical leaching or concentration of brine (or saltwater) using solar thermal storage batteries (or solar ponds), and subsequent separation of lithium by carbonate precipitation. However, these processes are complex, time-consuming, require large amounts of chemicals, or are strongly dependent on local weather conditions. For example, pre-concentration of brine using solar energy or wind can take 4-5 months or longer. Furthermore, these conventional methods suffer from many known problems, including the complexity of the design process, low Li recovery rates, and the difficulty in controlling impurity content. Brine is one of the most important sources of lithium. Recovering lithium from brine typically involves at least one of the following processes: adsorption, precipitation, ion exchange, and solvent extraction. However, because lithium and magnesium are chemically similar, separating them is difficult, and therefore the purity of lithium products recovered from brine is relatively low.

[0003] Furthermore, lithium can be reused (or recycled) from used lithium batteries and various types of lithium-containing waste. Currently, the industrial extraction of lithium from used lithium batteries is not practiced.

[0004] The process of Li + recovery (or recovery) based on membranes (or membranes) has been studied. However, there are only limited published reports. For example, nanofiltration (or nanofiltration), electrolysis (or electrolysis), electrodialysis (or electrodialysis), dialysis (or dialysis), membrane solvent extraction (or membrane solvent extraction) and membrane type adsorbents (or adsorbents) or mixed matrix membranes technology has been discussed. For example, nanofiltration of brine using a spiral wound Desal-5 DL 2540C membrane (GE Osmonics) resulted in a Li + / Mg 2+ separation factor (or separation factor) of 3.5 (X. Wen et al., Sep. Purif. Technol., 49 (2006), p: 230-236.). For the Desal-DK membrane (GE Osmonics), depending on the concentration of Li + and Mg 2+ in the feed (or feed) and their ratio, a Li + / Mg 2+ separation factor in the range of 2 - 3.2 was shown (Y. Gang et al., Chinese Journal of Chemical Engineering, 19 (2011), p: 586-591; S.-Y. Sun et al., Journal of Water Process Engineering, 7(2015), p:210-217).

[0005] Liu et al. (Colloids and Surfaces A: Physicochemical and Engineering Aspects, 468 (2015), p: 280-284) studied the influence of various parameters on the extraction performance (or extraction performance) of Li + from brine by electrodialysis tests. Under optimized operating conditions, the electrodes showed a remarkable Li + exchange capacity (or exchange capacity) of 38.9 mg / g.

[0006] Hoshino (Fusion Engineering and Design, 88 (2013), p: 2956-2959; Desalination 317 (2013), p: 11-16) reports on the use of an ionic liquid (N-methyl-N-propylpiperidium bis(trifluoromethanesulfonyl)imide) through which, during electrodialysis, only the major seawater ions (containing Na, Mg, Ca, and K, but not Li) permeate (or osmotic) from the anode to the cathode. + The solution can be concentrated at the anode and recovered by chemical precipitation with the addition of magnesium. However, monovalent ions (Na, K, and Li) could not be separated.

[0007] In another study, Hoshion (Desalination 359 (2015), p: 59-63) extracted lithium from seawater using electrodialysis with a Li-ion superconductor (or Li-ionic superconductor) (applied voltage: 2V). This showed better lithium selectivity compared to (Na, Mg, Ca, and K). Here, Li was extracted from seawater into the recovered solution. + The driving force for extraction was due to the electric potential. It was found that the actual recovery rate of lithium after 72 hours reached 7%. [Overview of the project] [Problems that the invention aims to solve]

[0008] However, existing lithium-selective films exhibit relatively low lithium selectivity and poor stability, limiting their practical applications.

[0009] The object of the present invention is to eliminate at least one drawback of the prior art and / or to provide a film that replaces the films of the prior art. [Means for solving the problem]

[0010] Where any or all of the terms “comprise,” “comprises,” “comprised,” or “comprising” are used herein (including in the claims), they should be interpreted as identifying the presence of a described feature, number, process, or component. However, they do not preclude the presence of one or more other features, numbers, processes, or components.

[0011] (Summary of the invention) A first aspect of the present invention provides a separation membrane (or separation membrane). This separation membrane comprises a target ion permeable polymer-ceramic composite material (or target ion permeable polymer-ceramic composite material), which comprises a target ion permeable ceramic (or target ion permeable ceramic) and at least one target ion permeable organic polymer (or target ion permeable organic polymer). This organic polymer is bonded (or associated with) the target ion permeable ceramic. Here, the membrane allows for the selective permeation (or penetration or permeation) of target ions through it.

[0012] Preferably, the membrane is a target ion separation membrane. More preferably, it is a membrane for separating the target ion from an aqueous solution. Preferably, the solution comprises the target ion and at least one other ion.

[0013] A second aspect of the present invention provides a membrane for separating lithium target ions from an aqueous solution of ions. The membrane comprises a lithium target ion porous support substrate (or lithium target ion porous support substrate) supporting a lithium target ion permeable polymer ceramic composite material. Here, the target ion-permeable polymer-ceramic composite material is Li 1.3 Al 0.3 Ti 1.7 It is a (PO4)3(LATP) ceramic that is bonded (or associated) with polyvinylidene fluoride (PVDF). Here, PVDF is present in the target ion-permeable polymer-ceramic composite at a concentration (wt%) of approximately 10:1 (ceramic:polymer).

[0014] Preferably, the aqueous solution comprises the target ion and at least one other ion.

[0015] A third aspect of the present invention provides a method for manufacturing a membrane, preferably an electrodialysis membrane. This manufacturing method comprises the following steps. A step (or process) of preparing a solution of a target ion-permeable ceramic material (preferably LATP) and at least one organic polymer (preferably PVDF) in a volatile organic solvent (preferably dimethylformamide (DMF)), The process (or step) of solution casting (or solution casting) this solution into a mold of a predetermined shape, A process (or step) of evaporating a solvent to form a film of a target ion-permeable polymer-ceramic-composite material.

[0016] A fourth aspect of the present invention provides a film that can be obtained (or is obtained) by the third aspect.

[0017] A fifth aspect of the present invention provides the use of a membrane according to the first or fourth aspect in a target ion separation technique, preferably a lithium ion separation technique, most preferably in electrodialysis.

[0018] A sixth aspect of the present invention provides an electrodialysis method for selective separation of lithium ions from brine or from lithium-containing solutions derived from lithium recycling methods. This method comprises the step of applying a voltage to a membrane according to the first or fourth aspect.

[0019] A seventh aspect of the present invention provides an electrodialysis stack comprising a membrane of the first or fourth aspect disposed between a pair of anion exchange membranes. [Brief explanation of the drawing]

[0020] [Figure 1] Figure 1 shows SEM images of LATP before ball milling (a,b), and SEM images (c) and XRD patterns (d) after ball milling. [Figure 2] Figure 2 shows SEM images of a pure PVDF membrane (a, c, e) and a LATP-P membrane (b, d, f). [Figure 3] Figure 3 shows the SEM image (a) and energy-dispersive X-ray (EDX) elemental mapping (C (b), Al (c), Ti (d), P (e), O (f)) of the LATP-P film. [Figure 4] Figure 4 shows a photograph of the electrodialysis system (a) and a schematic diagram of the electrodialysis stack (b). [Figure 5] Figure 5 shows a schematic diagram of the movement of Li+ ions through the LATP structure. The Li sites (pink spheres), consisting of Li1 (stable sites) and Li3 (transition sites), can be diffused through the crystal lattice using ions. The pink rods (or bars) represent Li diffusion channels, the blue octahedra represent TiO6 / AlO6, and the green tetrahedra represent PO4. [Figure 6]Figure 6 shows, a) a digital photograph of the LATP-PVDF composite film (scale bar: 5 cm), b) an XRD image, c) an XPS image, d) a SEM image of the skin layer (scale bar: 1 μm), e) a SEM image of the lower layer of the LATP-PVDF film (scale bar: 5 μm), f) a cross-sectional SEM image (scale bar: 50 μm), g) a cross-sectional SEM image of the skin layer (scale bar: 1 μm), and h) a cross-sectional SEM image of the lower layer (scale bar: 5 μm). [Figure 7] Figure 7 shows the lithium separation performance. a shows the concentrations of LiCl, NaCl, and MgCl2 ions on the permeate side (or permeate side or permeate side). b shows the corresponding ion flux of the membrane as a function of electrodialysis time (feed: 0.1 M single-ion solutions of LiCl, NaCl, and MgCl2, respectively). c shows the concentration of LiCl ions on the permeate side (or permeate side or permeate side). d shows the corresponding Li+ ion flux of the membrane as a function of electrodialysis time (feed: 0.1 M, 0.01 M, and 0.0001 M single-ion solutions of LiCl, respectively). e shows the concentrations of Li+, Na+, and Mg2+ ions on the permeate side (or permeate side or permeate side) based on ICP measurement. f represents the corresponding ion flux of the membrane (feed: 0.3 M mixed ion solution, LiCl:NaCl:MgCl2 = 1:1:1 (molar ratio)). All experiments were performed at room temperature. [Figure 8]Figure 8 shows the stability and real-world performance of the LATP-PVDF membrane. a shows the LiCl concentration on the permeate side (or permeate side or permeate side) after 7 electrodialysis and washing cycles using a fresh 0.1 M LiCl solution as the feed solution. b shows the LiCl concentrations in the feed and permeate solutions after a 160-hour continuous electrodialysis test using a 0.02 M LiCl feed solution. c shows the Li+ and other ion concentrations on the permeate side (or permeate side or permeate side) when synthetic brine water is used as the feed solution. d shows the corresponding ion flux of all available ions in the feed solution at the end of the electrodialysis (ED) test in c. e shows the Li+ and other ion concentrations on the permeate side (or permeate side or permeate side) when synthetic seawater is used as the feed solution. f represents the corresponding ion flux of all available ions in the feed solution at the end of the electrodialysis (ED) test of e. [Modes for carrying out the invention]

[0021] (Detailed description of the invention) The present invention provides a membrane for separating target ions from an aqueous solution of ions (e.g., a brine solution, or a solution containing lithium ions or lithium ions resulting from a lithium battery recycling process). The membrane comprises a target ion-permeable ceramic and at least one target ion-permeable organic polymer, the organic polymer being bonded (or associated with) the target ion-permeable ceramic. The membrane allows for the selective permeation (or penetration or permeation) of target ions through it. The membrane of the present invention comprises a target ion-permeable polymer-ceramic composite material (or target ion-permeable polymer-ceramic composite material or target ion-permeable polymer-ceramic composite material), which ionically conducts (or conducts ionically) the target ion of interest. Preferably, the membrane supports the selective permeation (or penetration or permeation) of a desired alkali metal ion through it. Preferably, the target ion is a lithium ion.

[0022] Preferably, at least one organic polymer may be in the form of a polymer matrix, where the ceramic particles are embedded or encapsulated. Preferably, at least one organic polymer coats or encapsulates at least a portion of the target ion-permeable ceramic particles. Preferably, at least one organic polymer coats or encapsulates all of the target ion-permeable ceramic particles. Preferably, the target ion-permeable ceramic particles are embedded in a matrix (or base material) of one or more organic polymers. Preferably, at least one organic polymer is selectively permeable to the target ions. Preferably, at least one organic polymer has a porous structure (or porous structure or porous structure). Preferably, the pores (or pores) of this organic polymer exclude ions that are not the target ions (e.g., non-lithium ions (or non-lithium ions)).

[0023] The ion-permeable ceramic may appropriately contain solid particles. These solid particles include grains, granules, crystals, crystallites, and particle aggregates (or particle aggregates).

[0024] Preferably, the ceramic particles have a specific average particle size distribution (or average particle diameter distribution, average particle size distribution, or average particle size distribution). For example, the ceramic particles may have a particle size distribution in the range of 200 nm to 50 μm. Particle aggregates of particles, granules, crystals, and crystallites may have a particle size distribution in the range of an average diameter of about 0.05 μm to about 50 μm, preferably an average diameter of about 0.1 μm to about 30 μm, more preferably an average diameter of about 0.2 μm to about 10 μm. Particle aggregates may arise from the sintering (or sintering) or compression (or compaction) of one or more particles, granules, crystals, and crystallites. Individual particles, granules, crystals, or crystallites may have a particle size distribution in the range of a diameter of 200 nm to about 300 nm. Crystals and crystallites may be polycrystalline or monocrystalline. Preferably, crystals or crystallites consist of one or more grains. Grains may be bonded to (or associated with) grain boundaries, which are surface defects or area defects that form an interface between grains of different orientations. Grains and crystallites in ceramic materials may not be constant (or may vary) in size (or dimensions) and orientation (or orientation). As used herein, the term "particles" is intended to encompass (or cover) particles, granules, crystals and crystallites, as well as particle aggregates (or particle assemblies). A preferred average particle size distribution may result from the grinding of the ceramic material (e.g., grinding by ball milling). Preferably, prior to ball milling, the average particle size of a preferred target ion-permeable ceramic may be 100 μm or larger. Preferably, the ceramic starting material may be ground (e.g., ground by a ball mill) to give a ceramic powder having a desired particle size range distribution. In one embodiment, the particles and particle aggregates may be substantially regular, irregular, or a mixture of regular and irregular shapes (for example, substantially cubic, rectangular, hexagonal, pyramidal, diamond-shaped, spherical, or elliptical shapes).In some embodiments, the shape is not fibrous or rod-shaped.

[0025] Preferably, the target ion-permeable polymer-ceramic composite material of the film is sintered and / or compressed one or more times. A preferred film comprises the target ion-permeable polymer-ceramic composite material, which is provided in the form of a plate-like sintered compact. In some embodiments, the plate-like sintered compact material comprises a material in which particles of the target ion-permeable ceramic take the form of an interlock structure of sintered, compressed and / or densely packed (or densified) ceramic particles. In some embodiments, some of the ceramic particles melt together to form aggregated (or agglomerated) ceramic particles. Densification occurs where the porosity (or porosity or void ratio or porosity) of the material decreases, thereby increasing the density of the material. Density can be reduced by increasing the packing of particles in a given area or volume (this can be achieved by reducing the particle size). Density is the average number of particles in a given unit volume or unit area of ​​the film (or measured value). In areas of the film with higher density, there are fewer gaps between ceramic particles. Conversely, in areas of lower density, there are more gaps between particles. In areas of higher density, a region of that unit area or unit volume has a higher average number of particles compared to areas of lower density. In areas of lower density, there are fewer average number of particles compared to areas of higher density. Regions containing smaller particles are understood to be denser (or higher density) because they have a higher average number of particles. Conversely, larger particles occupying the same area / volume are understood to be less dense because they have a lower average number of particles.

[0026] In other embodiments, grain boundaries between particles are formed during sintering and / or compression. Preferably, at least one organic polymer may fill the gaps between grain boundaries in the ceramic particles. The organic polymer may substantially fill all of the gaps between grain boundaries, or it may fill at least some of them. Advantageously, the gaps between the ceramic and at least one organic polymer may be further filled by incorporating (or including or incorporating) a second (or further) organic polymer.

[0027] Preferably, the target ion-permeable ceramic and at least one organic polymer may be present in the target ion-permeable polymer-ceramic composite at a concentration (wt%) ratio (ceramic:polymer) of about 1:1 to about 20:1, more preferably about 1:1 to about 15:1, and most preferably about 10:1. In some embodiments, the ceramic and at least one organic polymer are present in the composite at a concentration (wt%) ratio of about 1:1 to about 18:1, preferably about 5:1 to about 15:1, even more preferably about 8:1 to about 12:1, and most preferably about 10:1.

[0028] Described herein are membranes of target ion-permeable polymer-ceramic composite material for selectively permeating target ions (preferably lithium target ions) through the membrane. The membrane comprises a target ion-permeable ceramic and at least one organic polymer, the organic polymer bonded (or associated with) the target ion-permeable ceramic. Preferably, the membrane is selectively permeable (or permeable or permeable) to target ions when the membrane is under the influence of an electrical potential. The membrane may be appropriately subjected to an electrical potential.

[0029] Preferably, in the film of the present invention, the target ion-permeable ceramic particles in the target ion-permeable polymer-ceramic composite material are sintered. Preferably, the film does not contain a homogeneous (or uniform) dispersion (or dispersion) of ceramic particles in the polymer matrix. Preferably, the film comprises a heterogeneous (or non-uniform) dispersion (or dispersion) of ceramic particles in the polymer matrix.

[0030] Preferably, the target ion-permeable ceramic particles are compressed (or compacted) within the membrane. Suitablely, the compression (or compaction) of the ceramic particles throughout the polymer matrix is ​​not homogeneous (or uniform). Suitablely, the compression of the ceramic particles throughout the polymer matrix is ​​heterogeneous (or non-uniform).

[0031] Preferably, the level of compression is not constant (or variable) across the vertical cross-section of the film. This means that the level of compression (or compaction level) of the target ion-permeable ceramic does not have to be constant (or may be variable) across the vertical cross-section of the film. In some embodiments, the level of target ion-permeable compaction decreases across the vertical cross-section of the film in the form of a decreasing compression gradient (or compaction gradient) of particles. In some embodiments, the level of density of the target ion-permeable ceramic decreases across the vertical cross-section of the film in the form of a decreasing density gradient (or density gradient) of particles. In some embodiments, the level of a particular size (or dimension) of the target ion-permeable ceramic decreases across the vertical cross-section of the film in the form of a decreasing size (or dimension) gradient (or size gradient) of particles.

[0032] Preferably, the target ion-permeable polymer-ceramic composite may include at least two regions, where the first region comprises a rich region (or abundant region or high region) of the target ion-permeable ceramic, which comprises densely packed particles of the target ion-permeable ceramic; and the second region comprises particles that are less densely packed with the target ion-permeable ceramic compared to the first region. In some embodiments, the preferred film may include at least one subsequent region, which comprises particles that are less densely packed with the target ion-permeable ceramic than the preceding region.

[0033] In some embodiments, the target ion-permeable polymer-ceramic composite may comprise at least two layers, where the first layer comprises a rich layer (or abundant layer or many layer) of target ion-permeable ceramic, which comprises particles of target ion-permeable ceramic; and the second layer is a rich layer (or abundant layer or many layer) of organic polymer, where the first layer comprises more particles of target ion-permeable ceramic compared to the rich layer (or abundant layer or many layer) of organic polymer.

[0034] Preferably, during manufacturing, a solvent suspension (or solvent suspension) of the target ion-permeable ceramic composite and at least one organic polymer is cast into a vessel having the desired membrane shape. Evaporation of the solvent from the solution results in the formation of a membrane having the desired microstructure as described above. Where the ceramic material contains a particle size distribution of large and small ceramic particles, during the solvent evaporation process, larger ceramic particles preferentially migrate to the lower (or bottom) region of the cast suspension, while smaller particles remain suspended in the upper (or upper) region of the cast suspension. As the solvent evaporates, the particles become densely packed with each other and embedded (or buried) in the polymer matrix formed during evaporation. In the lower region of the membrane, the sedimentation and compression of larger particles leave relatively large gaps and spaces (porosity) between the particles, which are filled by the polymer matrix, making the lower region of the membrane porous. In contrast, in the upper region of the membrane, smaller particles are compressed, forming regions of higher density ceramic particles, which result in very small gaps and spaces between the ceramic particles. Because the gaps and spaces are smaller in the upper region, less polymer is needed to fill these gaps and spaces. This results in a membrane with regions of different particle densities and different polymer densities. In some embodiments, the resulting microstructure may take the form of a particle size gradient across the vertical cross-section of the membrane. Larger, less densely packed ceramic particles are present in the lower region of the membrane, while smaller, more densely packed ceramic particles are present in the upper region of the membrane. The organic polymer matrix can be found throughout the entire membrane region. However, the amount is not constant (or changes) in proportion to the size (or dimensions) of the gaps or spaces between the ceramic particles.Therefore, a preferred film comprises regions rich in ceramic particles and regions rich in polymer. In some embodiments, the intermediate regions of the film comprise instantaneous (or immediate) particle-sized ceramic particles having gaps and spaces of corresponding intermediate sizes between the particles.

[0035] In one embodiment, the ion-permeable ceramic may be formed by a solid-state reaction (such as coprecipitation, sol-gel, or melt-quenching, preferably sol-gel). Preferably, the ceramic is substantially pure and free from impurity phases, and such impurity phases are identifiable using techniques such as scanning electron microscopy (SEM) imaging and / or X-ray diffraction (XRD) analysis. Preferably, the target ion-permeable ceramic may be a lithium superionic conductor (or lithium super-ionic conductor), which has lithium ion channels and includes LISICON type, argyrodites, LGPS, and LMPS compounds. Preferably, the ceramic material is selected from NASICON or LISICON material, and preferably, as the ceramic material, LATP(Li 1+x Al x Ti 2-x (PO4)3, x=0.3~0.4), and most preferably Li 1.3 Al 0.3 Ti 1.7 The material is (PO4)3, which has excellent water stability and lithium ion conductivity. In one embodiment, the target ion permeable ceramic is an LATP ceramic, which preferably has a crystalline phase and morphology (or form) as shown by the XRD pattern and SEM image in Figure 1, respectively. Preferably, the LATP ceramic is crystalline and has, for example, a rhombohedral lattice as confirmed by X-ray diffraction. A preferred LATP ceramic is free of impurities, particularly AlPO4 impurities.

[0036] Appropriately, an ion-permeable ceramic comprises a plurality of ion transport channels that selectively allow the movement, transport, or passage of ions through the ceramic material. Preferably, the ion channels are metallic ion channels. The movement, transport, or passage of ions is considered to occur from one side of the composite to the other, for example, opposite sides of the composite. If the composite is in the form of a film, the opposite sides correspond to opposite surfaces.

[0037] Preferably, the interface between the target ion-permeable ceramic and at least one organic polymer, and the interface between the organic polymer and the target ion-permeable ceramic, are intertwined and / or interwelded. Advantageously, this can result in a particularly strong physical bond (or adhesion) between the organic polymer and the target ion-permeable ceramic. In some embodiments, the polymer may enter and exit (or enter) at least some of the target ion transport channels in the ceramic.

[0038] Preferably, the target ion-permeable polymer-ceramic composite comprises at least two layers (a first layer and a second layer). Here, the first layer comprises a rich layer (or abundant layer or rich layer) of target ion-permeable ceramic, which comprises particles of target ion-permeable ceramic. The second layer is a rich layer (or abundant layer or rich layer) of organic polymer. Here, the first layer comprises more target ion-permeable ceramic particles than the rich layer of organic polymer. The rich layer of target ion-permeable ceramic is understood to comprise more particles of ceramic material than the rich layer of organic polymer. Preferably, the second layer may form an outer coating (or outer film) on the inner body (or inner body) (which comprises the first layer of target ion-permeable ceramic).

[0039] Furthermore, the ion-permeable polymer-ceramic composite may consist of three layers. Thereafter, the ceramic material forms a ceramic interlayer, which is bonded to opposing surfaces by at least one organic polymer layer. In another embodiment, the arrangement (or alignment or arrangement) of the interlayer may be constrained by further layers of different organic polymers to form a more complex ion-permeable polymer-ceramic composite structure. In a particular embodiment, at least one organic polymer coats (or covers) opposing surfaces of the target ion-permeable ceramic. The polymer coating may be the same or different on the opposing surfaces.

[0040] In some embodiments, target ion-permeable ceramic particles are bonded (or associated with or linked to) at least one organic polymer by one or more of the methods described herein.

[0041] In some embodiments, the ceramic and the first organic polymer (bonded to (or associated with or linked to) the ceramic) are in the form of a coating of particles and / or a coating of a layer of ceramic material. Preferably, at least one organic polymer may coat at least a portion of the particles (and particle aggregates (or assemblies)) of the target ion-permeable ceramic. In other embodiments, some (but not all) (a small number (or minority)) of the ceramic particles may be coated with the organic polymer. In some embodiments, a larger proportion (or majority) of the particles of the target ion-permeable ceramic are coated with the organic polymer compared to those that are not. In other embodiments, the majority of each particle of the ceramic are uncoated (or uncoated). In other embodiments, at least one organic polymer coats substantially all of the particles of the target ion-permeable ceramic.

[0042] The coating may, if desired, contain two or more organic polymers. For example, it may be in the form of a single copolymer coating, or separate coatings of individual polymers, or separate coatings of copolymers or a combination thereof. In some embodiments, the organic polymers bond (or associate or associate) with the target ion-permeable ceramic to form a target ion-permeable polymer-ceramic composite of the film, and such organic polymers include a combination of two or more separate layers of organic polymers. The individual polymer coatings may be the same polymer or different polymers.

[0043] Preferably, at least one organic polymer is a hydrophilic polymer, or a combination or blend (or mixture) of two or more organic polymers. The organic polymer may be selected from the group consisting of polyvinylidene fluoride (PVDF), sulfonated tetrafluoroethylene-based fluoropolymer copolymers (e.g., Nafion), chitosan, polysulfone, and combinations thereof. Most preferably, the organic polymer is PVDF. PVDF is a commercially available film material with excellent thermal stability, mechanical strength, and chemical resistance. High molecular weight PVDF having a molecular weight of 200 kDa to 600 kDa is preferred. PVDF having a molecular weight of 450 kDa to 575 kDa is more preferred. In one embodiment, PVDF having a molecular weight of 534 kDa is particularly preferred.

[0044] In some embodiments, a blend or two or more organic polymers may be used, preferably PVDF and Nafion. When PVDF and Nafion are included, Nafion may suitably be provided in the form of an overcoat on the PVDF coating. The second polymer may be provided as a second coating on the first coating of the organic polymer or as an additive. In one embodiment, by including the second organic polymer, Li + / K +The selectivity is increased. In one embodiment, Nafion has been found to be an excellent second organic polymer. For example, in one embodiment, a thin Nafion layer of 1 micron (μm) is coated on top of a first coating of an organic polymer, Li + / Na + The selectivity increases from 9.64 to 13.33.

[0045] Preferably, the lithium-ion permeable ceramic is LATP, the organic polymer is PVDF, or the organic polymer is a combination of PVDF and Nafion.

[0046] Particles, i.e., individual particles, grains, granules, and / or aggregates (or agglomerations) of target ion-permeable ceramics, may be substantially or completely wrapped or coated, or partially wrapped or coated, by at least one organic polymer. The wrapping or coating may be obtained from one or more layers or coats of polymer or copolymer, e.g., from a first or second layer of the same or different organic polymer. Appropriately, such an effect may embed (or bury) the ceramic particles in the polymer matrix.

[0047] In some embodiments, particles of a target ion-permeable ceramic may form a first layer of the ceramic material. The ceramic material itself may be coated with one or more further layers of organic polymer. In another embodiment, the ceramic material is placed between layers of organic polymer; for example, the ceramic material is sandwiched between one or more layers of organic polymer to provide an intermediate layer of the ceramic material. For example, the ceramic material may be sandwiched between PVDF layers and then further sandwiched with Nafion.

[0048] Preferably, the target ion-permeable polymer-ceramic composite is provided in a planar or plate-like shape. Planar shape is understood to mean that the film has substantially larger dimensions in two directions relative to one direction. In other words, the film is substantially 2D in shape, as opposed to 3D in shape. The film may be plate-like, preferably disc-shaped, square, or rectangular. The shape may appropriately include plate-like or disc-shaped configurations. However, it may also be provided in the form of a rollable sheet of film material. Preferably, the ion-permeable ceramic is provided on a substrate in the form of a sintered plate-like compact.

[0049] Appropriately, the ion-permeable membrane has selective permeability (or permeability) to one or more target ions and excludes other undesirable ions. Preferably, the target ions are metal ions. Appropriately, the metal ions are monovalent cations, preferably alkali ions, most preferably sodium ions or lithium ions, and particularly lithium ions. Other alkali ions include potassium, rubidium, and cesium. In one embodiment, the ion-permeable membrane is a non-lithium monovalent ion (K + na + It does not have permeability (or penetration) to divalent and trivalent metal ions (for example, Mg 2+ It does not have permeability (or penetration) to ). Selectivity for lithium ions is particularly preferred. Preferably, the selectivity is for bare ions (or bare ions), that is, for metal ions that are not hydrated ion species, such as lithium ions, which is in contrast to hydrated lithium ions.

[0050] Preferably, the organic polymer is permeable (or permeable) to the target metal ion, preferably lithium ion. More preferably, it is selectively permeable to the target metal ion, preferably lithium ion. Even more preferably, the organic polymer is permeable to the target metal ion, preferably lithium ion, under the influence of electrical potential.

[0051] Preferably, the lithium ion permeable ceramic has a capacitance of 1 × 10 at 25°C. -4 Scm -1 It has a lithium-ion conductivity (or lithium-ion conductivity or lithium-ion conductivity) greater than 1 × 10⁻¹⁰, more preferably 1 × 10⁻¹⁰. -3 Scm -1 It has a higher lithium ion conductivity than [another material]. The lithium ion permeable composite preferably has a conductivity of 1 × 10⁻⁶ at 25°C. -4 Scm -1 It has a lithium-ion conductivity greater than that, more preferably 1 × 10⁻⁶ -3 Scm -1 It has a lithium-ion conductivity greater than that of [another material]. Preferably, the target ion-permeable ceramic is a lithium superionic conductor material (or lithium superionic conductor material).

[0052] Such a membrane is useful for recovering lithium ions from liquid solutions (particularly aqueous solutions such as brine). This membrane makes it possible to extract lithium from the solution. The solution is concentrated, and the lithium is concentrated to a concentration level equal to the solubility of a particular lithium salt of interest. Recovering lithium from high-concentration lithium solutions is easier from the standpoint of economic viability. However, in principle, it is possible to recover substantially all lithium ions from any desired solution (even at the ppm level, e.g., around 1 ppm). In particular, in the experiments described herein, the inventors have demonstrated effective recovery from solutions having concentrations of 300 ppm and 1000 ppm.

[0053] In a preferred embodiment, the present invention provides a membrane for separating lithium target ions from an aqueous solution of ions. Such a membrane may comprise a lithium target ion porous support substrate (or lithium target ion porous support substrate) that supports (or supports) a lithium target ion permeable polymer-ceramic composite material (or lithium target ion permeable polymer-ceramic composite material). The target ion permeable polymer-ceramic composite material comprises Li bonded (or associated with) polyvinylidene fluoride (PVDF). 1.3 Al 0.3 Ti 1.7 (PO4)3(LATP) ceramic may be used. Preferably, PVDF may be present in the target ion-permeable polymer-ceramic composite at a concentration (wt%) ratio of approximately 10:1 (ceramic:polymer).

[0054] Furthermore, a membrane comprising the following will be described. Target ion porous support substrate, Target ion-permeable polymer-ceramic composite material (supported by a porous support substrate) Here, the target ion-permeable polymer-ceramic composite material comprises a target ion-permeable ceramic and at least one organic polymer (which is bonded (or associated with) the target ion-permeable ceramic). Here, the film is designed to selectively permeate target ions, preferably lithium-target ions, through the film.

[0055] Furthermore, a lithium-ion permeable membrane (or osmotic membrane) (or lithium-ion permeable membrane) for selectively permeating lithium target ions will be described. This membrane includes the following: Lithium-target ion porous support substrate Lithium-target ion-permeable polymer-ceramic composite material (supported by a porous support substrate) Here, the target ion-permeable polymer-ceramic composite material comprises LATP ceramic and at least one organic polymer (which comprises PVDF bonded (or associated or linked with) the target ion-permeable ceramic). Here, at least one organic polymer is present in the target ion-permeable polymer-ceramic composite at a concentration (wt%) ratio of approximately 10:1 (ceramic:polymer).

[0056] Ideally, the ion-permeable membrane is supported (or assisted) by a target ion-porous support substrate.

[0057] In the first embodiment, the target ion-permeable polymer-ceramic composite described above can be used alone (or standalone) as a membrane. On the other hand, in some embodiments, supporting the target ion-permeable polymer-ceramic composite material with a target ion-porous support substrate is advantageous because it allows thinner layers of the target ion-permeable polymer-ceramic composite material to be used in the relevant separation applications.

[0058] Preferably, the substrate support has an average thickness smaller than the thickness of the target ion-permeable polymer-ceramic composite.

[0059] Preferably, the target ion porous substrate support may be a synthetic fabric (or synthetic fabric product) which is woven or nonwoven. The fabric (or fabric product) may be formed from one or more of the following: Polyethylene, polypropylene, polyacrylonitrile, polyvinyl chloride, polyester, polyamide, and copolymers thereof, or porous membranes (e.g., polysulfone, polyethersulfone, polyphenylenesulfone, polyphenylene sulfide, polyimide, polyetheramide, polyamide, polyamideimide, polyacrylonitrile, polycarbonate, polyacrylate, cellulose acetate, polypropylene, poly(4-methyl-1-pentene), polyinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, polychlorotrifluoroethylene, and those based on copolymers thereof) In a preferred embodiment, the substrate support comprises porous (or porous) nylon or porous (or porous) alumina.

[0060] The membrane of the present invention can be used in separation techniques, preferably in dialysis or electrodialysis.

[0061] The membrane may be used in separation techniques, preferably dialysis or electrodialysis, most preferably lithium ion dialysis or electrodialysis separation techniques. Suitablely, lithium ion separation techniques include the separation of lithium ions from saline solutions (e.g., brine, seawater, or aqueous solutions derived from lithium ion recycling or recovery processes).

[0062] An electrodialysis method for selectively separating lithium ions from a saline solution (preferably brine or an aqueous solution derived from a lithium ion recycling or recovery process) comprises the step (or process) of applying a voltage to a membrane according to a first or second embodiment. The electrodialysis stack (or electrodialysis stack) may comprise one or more membranes as described herein. In the electrodialysis stack, each membrane may be positioned between a pair of anion exchange membranes. Preferably, a preferred electrodialysis stack comprises a plurality of membranes, each membrane positioned between a pair of anion exchange membranes.

[0063] The present invention also relates to a method (or process) for producing a membrane (preferably a membrane for electrodialysis) as described. Such a method may include preparing a solution (or step) of a target ion-permeable ceramic material (preferably LATP) and at least one organic polymer (preferably PVDF). Preferably, this solution is prepared in an organic solvent, preferably a volatile organic solvent such as dimethylformamide (DMF). The resulting solution can be stirred for, for example, 24 hours until a suspension is formed. The membrane can then be formed by solvent casting (or casting the solution) into a mold (or form) of a predetermined shape, for example, a plate (or form). A suitable mold (or form) is a glass container. The solvent may then be evaporated to form a membrane (or membrane) of the target ion-permeable polymer-ceramic composite material. Preferably, the step (or process) of evaporating the solvent includes evaporation (or evaporation) via a solvent evaporation-induced phase separation (or solvent evaporation-induced phase separation) (SEIPS) process. Depending on the desired film size (or dimensions), the evaporation step may take up to 24 hours. Evaporation may be assisted (or aided) by temperature. For example, good results have been achieved by evaporating the solvent at about 60°C.

[0064] In one embodiment, a preferred film may be manufactured from a solvent evaporation-induced phase separation (SEIPS) process. In this embodiment, ceramic particles are embedded in one or more polymer materials. One or more polymers are in the form of a matrix surrounding the ceramic particles. The density of ceramic particles and polymers in the composite varies from region to region. In other words, the ceramic particles are not homogeneously dispersed in the polymer matrix. The film does not have a single ceramic density or a single polymer density. Rather, the dispersion of particles and polymers is heterogeneous, thereby giving a specific microstructure. This includes non-constant (or variable or variable) particle densities and non-constant (or variable or variable) polymer densities in different horizontal regions of the film. In some embodiments, a preferred microstructure includes a film having a high-density upper layer (or upper region) with reduced porosity (or porosity or voids or porosity) and a lower-density lower layer (or bottom layer) or lower region with increased porosity (or porosity or voids or porosity). The lower layer or lower region corresponds to the portion of the film closest to the mold (or template) during manufacturing. Cross-sectional SEM images of such a film may relate to a specific microstructure, which may result from the arrangement of ceramic particles and, further, from how they are embedded (or embedded) within the polymer matrix. For example, smaller ceramic particles may be located in the upper region (or upper region) of the film (closer to the skin layer (or surface layer)). On the other hand, larger ceramic particles may be located in the lower region (or bottom region) of the film. In some embodiments, intermediate-sized particles may be located in the intermediate region of the film. These layers or regions refer to the vertical cross-sectional regions passing through the top and bottom surfaces of the film.

[0065] Preferably, a preferred microstructure is one in which a size (or dimensional) gradient (or size gradient) of ceramic particles runs across the vertical cross-section of the film. Preferably, a preferred microstructure is one in which a density (or density gradient) of ceramic particles runs across the vertical cross-section of the film. A preferred microstructure has a polymer density inversely proportional to the density gradient or size gradient of ceramic particles in a particular horizontal region of the film. Preferably, smaller, more compressed ceramic particles are located in the upper layer or upper region of the film where the particle density is higher. Preferably, larger, less compressed ceramic particles are located in the lower layer or lower region of the film where the particle density is lower. Conversely, the upper layer or upper region of the film contains a smaller proportion of polymer compared to the lower layer or lower region of the film where the particle density is lower and contains a larger proportion of polymer. In some embodiments, this microstructure may be related to a high flux of target ions through the film.

[0066] One method for forming a film with a desirable microstructure involves rapidly settling larger aggregates (or aggregates) of ceramic particles during a solvent evaporation-induced phase separation (SEIPS) process. During SEIPS, as the solvent evaporates beyond the polymer's solubility limit, the polymer continues to absorb water vapor from the atmosphere (preferably 40-60% humidity). The polymer then undergoes phase separation, and a dense film of solid-phase polymer slowly forms around the ceramic precipitate. The interparticle spaces (or inter-particle spaces) between the polymer-filled ceramic particles become even narrower. At this point, the polymer gradually undergoes a phase change from fluid to glassy. The completion of SEIPS results in a ceramic-polymer film, which contains a dense upper layer or upper region and a ceramic-polymer mixed matrix.

[0067] In some embodiments, non-constant (or variable) compression (or compaction) or gradient (or gradient) structures may be used to support (or assist) the achievement of high-performance membranes (or high-performance membranes), for example, because ion permeability can be affected by the thickness of the membrane. The asymmetric microstructures / gradient structures described (e.g., the cross-section shown in Figure 6f) may enable faster ion transport. In this case, the upper (or top) / upper (or upper) layer(s) or upper (or top) / upper (or upper) region(s) act as a selective barrier, while the lower (or bottom) layer(s) or lower (or bottom) region(s) provide the membrane with mechanical strength and rigidity.

[0068] In such embodiments, the overall ionic conductivity (or ionic conductivity or ionic conductivity) of the film is based on the regional conductivity across the cross-section of the film between the skin layer (or surface layer) and the bottom layer (or lower layer). For example, PVDF chains have very low conductivity (10 -12 It has a conductivity (on the order of S / cm) and helps to give this film excellent mechanical properties and chemical resistance. On the other hand, the total conductivity (or total conductivity or total conductivity) of LATP particles is derived from (or a result of) the conductivity (or grain conductivity or grain conductivity) and grain boundary resistance (or grain boundary resistance) of the grains, where the conductivity across (or over) the grain boundaries is several orders of magnitude smaller. One ideal structure of the film may include a dense, selective barrier (or dense selective barrier) which gives the film high lithium selectivity. This barrier may give the film a cross-section that allows for high-speed ion transport across the film. Ion transport is likely to be dominated by both an upper layer (one or more) or upper region and a more porous lower support layer (one or more) or support region.

[0069] (Description of Embodiments of the Invention) The inventors have fabricated an asymmetric lithium-selective mixed matrix membrane (or film) based on a NASICON-type LATP superionic conductor (or NASICON-type LATP superionic conductor) and PVDF. Using this LATP-PVDF membrane, the inventors have demonstrated the ability to recover lithium at low energy from various sources (e.g., seawater with lithium ions in the range of 100-200 ppb). [Examples]

[0070] Example 1 We have developed polymer-based membranes for lithium extraction, particularly polymer-based membranes for lithium extraction by electrodialysis processes. Polymer-based membranes offer many advantages (e.g., high acid resistance, low cost, high long-term stability, and ease of scale-up). This disclosure describes a polymer-based lithium extraction membrane that exhibited excellent single-Li ion selectivity and high Li ion permeability (or permeation). The selectivity remained stable even after 15 days. The method reported in this study is easily scalable.

[0071] Membrane preparation Li 1.3 Al 0.3 Ti 1.7(PO4)3(LATP) is a NASICON-type compound that exhibited the highest lithium conductivity (or lithium conductivity or lithium conductivity) at room temperature. First, LATP was prepared by the sol-gel method. Briefly, a mixture of 1.46 g of lithium nitrate and 1.24 g of aluminum nitrate was dissolved in distilled water in a constant molar ratio and then stirred at room temperature for 1 hour. 5.3 g of titanium isopropoxide was slowly added to this dispersion. Then, an aqueous solution (containing 3.79 g of diammonium hydrogen orthophosphate pre-dissolved) was added with vigorous stirring. After stirring continued for 6 hours, a well-mixed solution was obtained. The final mixture was left to stand at room temperature for a further 48 hours, then heated to 100°C and held for 3 hours to evaporate the aqueous solvent. Next, this solid was heated at 900°C for 2 hours at a rate of 5°C min. -1 The mixture was fired at a slow heating rate, cooled to room temperature, and then ground into a fine powder. Next, the resulting dry gel was heated at 900°C for 2 hours at a rate of 1°C min. -1 Firing is performed at the following heating rate, 5℃ min -1 After cooling at the specified cooling rate, the powder was ground to obtain a fine powder with a particle size of 0.1–2 μm. This powder was then ground using a ball mill. The crystalline phase and morphology of LATP are shown in SEM images and XRD patterns in Figure 1. Figure 1(a,b) shows that the particle size is approximately 100 μm, while after ball milling it is 10 μm, indicating a significant reduction. In Figure 1(d), no impurity phases are observed, indicating that this powder is a pure LATP phase.

[0072] Next, LATP (5%, wt%) and PVDF (5%, wt%, Mw=180k) were dissolved in DMF and stirred for 24 hours. Then, 5 ml of the suspension was poured into a 9 cm Petri dish and dried at 60°C for 4 hours. Longer evaporation times may be used for larger films. This sample is referred to as LATP-P. Compared to a pure PVDF film (see Figure 2(a, c, e)), the LATP is successfully encapsulated (or wrapped) in the PVDF (see Figure 2b, d, f). This morphology can be further confirmed by EDX mapping analysis (see Figure 3). This result indicates that all LATP particles are well encapsulated (or wrapped) and dispersed between the layers of PVDF.

[0073] To optimize the ratio of LATP to polymer (PVDF), LATP-P membranes with different LATP-PVDF ratios (LATP-P-1 (2:1) and LATP-P-2 (10:1)) were prepared. Furthermore, a membrane referred to in this disclosure as LATP-PH (5:1) was prepared using high molecular weight PVDF (Mw=534k).

[0074] Preparation (or setup) of the electrodialysis stack. Figure 8(a,b) shows a schematic diagram of a system comprising an electrodialysis stack. Three solutions (i.e., lithium concentrate (or lithium-concentrated solution or lithium concentrate), lithium feed solution (or lithium feed solution or lithium feed solution), and electrode solution (or electrode solution)) are sequentially introduced into the column between the membranes. Specific amounts of LiCl, NaCl, and MgCl2 are used as the lithium feed solution. A 300 ppm NaCl solution is used as the electrode solution. Over time, lithium is gradually concentrated in the lithium concentrate solution.

[0075] This system was operated at 2–5V, achieving a maximum lithium extraction rate of 70%. The sample demonstrated a maximum lithium / magnesium selectivity of 46 and a maximum lithium / sodium selectivity of 10 (see Table 1). Other polymers (e.g., Nafion (LATP-N), chitosan (LATP-C), and polysulfone (LATP-PS)) were also investigated. These tests revealed that PVDF is a preferred candidate for membrane preparation.

[0076] [Table 1]

[0077] Table 2 compares the lithium extraction performance of other LATP-P(x) membranes. By increasing the LATP ratio in the LATP-P membrane, Li + It can be seen that the flux can be improved. LATP-P-2 is 23.06 g / (m³). 2 ·h) showed the highest Li flux. + / Mg 2+ and Li + / Na + The selectivity for each was 46.12 and 9.468, respectively.

[0078] [Table 2]

[0079] Furthermore, in order to confirm selectivity, the inventors tested LATP-P-2 using a mixture of LiCl / NaCl / MgCl2 (300 ppm) as the feed solution. + Except for Na + and Mg 2+ All of them were rejected. + The flux is 0.5 g / (m 2 It was found that it is h) Li + The flux was relatively low, but Li +It was confirmed that only [specific substance] could permeate the LATP-P membrane. This indicates that LATP-P exhibits superior performance in lithium recovery from mixed solutions.

[0080] System scaling The inventors of the present invention have found Li + A larger electrodialysis system was assembled for extraction. In this experiment, 1000 ppm LiCl / MgCl / NaCl was used as the feed solution. The operating potential was 20 V. + The flux is 48.26 g / (m 2 ·h) was the result. The recovery rate achieved was 98.5%. Li + / Mg 2+ and Li + / Na + The selectivity values ​​were 39.6 and 10.3, respectively.

[0081] Example 2 In another exemplary embodiment, the inventors have provided a lithium superionic conductor (or lithium superionic conductor) (Li 1.3 Al 0.3 Ti 1.7 A lithium-selective membrane (or solution-processable lithium-selective membrane) that can be processed in solution was fabricated from a composite (or complex) of (PO4)3) and polyvinylidene fluoride (PVDF). When this membrane was tested in an electrodialysis (ED) setup using synthetic salt brine (or synthetic salt brine) as the feed solution, Li + / Na + and Li + / Mg 2+The selectivity achieved were 9107 and 2239, respectively. Compared to conventional lithium mining, the lithium recovery process of this disclosure is energy-efficient, consuming 1.84 kWh of electricity (per kg of lithium chloride) from brine. Most importantly, this membrane can extract lithium ions from water sources with lithium ion concentrations as low as 170 ppb. Such scalable selective membranes offer a new path for sustainable lithium mining.

[0082] LATP particles were analyzed using the sol-gel method (Kunshina, G et al., Russian Journal of Inorganic Chemistry 59, 424-430 (2014)). No AlPO4 was detected as an impurity in the LATP particles. Powder X-ray diffraction (XRD) was used to analyze the structure of the LATP compounds. XRD patterns were obtained using a Miniflex 600 diffractometer (Rigaku, Japan) with Cu-Kα irradiation (15 mA, 40 kV) in the 2θ range (10-60°), at a 2° min interval. -1 The scan rates were obtained at room temperature. Surface morphology, film thickness, and composition were studied using a field emission scanning electron microscope (FESEM) (or field emission scanning electron microscope) (FESEM) operated at 5kV using a Nova NanoSEM 450 (FEI, USA). All samples were coated with platinum before SEM examination. X-ray photoelectron spectroscopy (or X-ray photoelectron spectroscopy) (XPS) was performed using a VG Multilab 2000 photoelectron spectrometer (VG Inc.), 2 × 10⁻¹⁶ -6The samples were characterized by monochromatic Al Kα irradiation with Pa. Binding energies were referenced to the 284.8 eV C 1s peak of surface adventitious carbon in the samples. Using synthetic brine and seawater as feeds (or supplies), the ion concentrations of the permeate (or osmotic solution or permeate solution) were measured using a Perkin-Elmer NexION 2000 ICP mass spectrometer. The ion concentrations of the permeate were measured at an external testing laboratory, ALS, for equimolarly mixed ion feeds (or ion supplies).

[0083] LATP-PVDF membranes were prepared by solvent evaporation-induced phase separation (SEIPS). A predetermined amount of LATP powder was mixed with polyvinylidene difluoride (PVDF) in dimethylformamide (DMF). This mixture was stirred at 80°C for 8 hours. The mixture was then transferred to a flat-bottom glass container and subjected to SEIPS for 6 hours. After heating at 60°C for 12 hours, the LATP-PVDF membrane was recovered. LATP-PVDF membranes were prepared by casting the LATP-PVDF doped solution into a glass container. Here, the solution underwent solvent evaporation-induced phase separation (SEIPS), resulting in the formation of an off-white membrane (Figure 6a).

[0084] To highlight the scalability (or scaling capability) of LATP-PVDF film production, a 25 cm × 30 cm film sheet was prepared (Figure 6a). The LATP-PVDF film exhibited similar XRD characteristic peaks and XPS spectra to the LATP powder (Figures 6b and 6c). This suggests that the pure LATP phase was maintained even after processing into the LATP film. SEM images of the upper layer (or top layer) (Figure 6f) and lower layer (or bottom layer) (Figure 6f) of the LATP-PVDF film revealed a dense skin layer (or surface layer or dense skin layer) and a porous bottom layer (or porous bottom layer). The "skin layer (or surface layer)" refers to the upper layer (or upper layer) facing the air. On the other hand, the bottom layer (or lower layer or lower layer or bottom layer) refers to the layer facing the glass container during SEIPS. SEM images of the vertical cross-section of the LATP-PVDF membrane revealed a heterogeneous (or non-uniform) microstructure. This structure comprises an asymmetric or density gradient (or density gradient) of the size (or dimensions or particle diameter or particle size) of the ceramic particles, and an asymmetric compression gradient (or compaction gradient) of the ceramic particles. Such a structure consists of LATP particles embedded (or embedded) within the matrix of the PVDF polymer (Figure 6f). Here, the size gradient (or size gradient) of the ceramic particles is evident, resulting in the non-constant (or variable or variable) density and compression of the particles. Smaller, more compressed LATP particles were observed closer to the skin layer (Figure 6g), while larger LATP particles were found near the bottom section of the membrane (Figure 6h) (where less compression is applied and the region is more porous). This unique microstructure is desirable and is obtained from the rapid sedimentation of larger aggregates (or condensates) of LATP particles during SEIPS. Conventionally, membrane solutions undergoing SEIPS often result in isotropic and low-porosity structures. For example, when a pure PVDF membrane was fabricated, an isotropic and porous structure was observed. In this case, the asymmetric structure required for high flux was achieved.During SEIPS, the solvent continued to evaporate beyond the solubility limit of PVDF, while the PVDF continued to absorb water vapor from the atmosphere (humidity 40-60%). As a result, the PVDF underwent phase separation, slowly forming a dense film of solid PVDF around the LATP precipitate.

[0085] The interparticle spaces (or gaps) between PVDF-doped LATP particles narrowed as the PVDF dope gradually transitioned from a fluid (or fluid) to a glassy (or glassy) state. Upon completion of SEIPS, an LATP-PVDF film was formed, which has a denser upper layer (or top layer) and a LATP / PVDF mixed matrix. A schematic diagram of the formation of the LATP-PVDF film by SEIPS is available in Figure 5.

[0086] The LATP-PVDF membrane developed in this study is designed for lithium recovery by electrodialysis, with one side of the membrane (e.g., upper layer / surface layer (or skin layer) (but not limited to)) facing the feed solution and the other side (e.g., lower layer (or bottom layer) (but not limited to)) facing the permeate solution (or permeate solution or permeate solution) (product solution). The conductivity (or conductivity) of the permeate site is in the range of 0.055 μS / cm to 202.2 mS / cm, that is, between the conductivity (or conductivity) of deionized water and concentrated LiCl solution. The actual conductivity (or conductivity) of the permeate solution depends on the parameters of the ED process (e.g., current density, temperature, pH, etc.) and the composition of the feed (or feed) (e.g., brine, seawater, Li recycling feed source (or Li recycling feed source), etc.). By selecting SEIPS and fabricating an asymmetric LATP-PVDF membrane, at least 10 -4 High Li (S / cm or higher) + A film can be obtained that achieves conductivity (conductivity close to that of a liquid electrolyte). Therefore, regardless of the concentration of the permeate solution, high Li +Fluxing has become possible. Furthermore, the unique LATP-PVDF structure achieved by SEIPS is also expected to reduce the electrical resistance of the membrane when current is applied to electrodes located at both ends of an electrodialysis (ED) cell.

[0087] The dense PVDF component of the LATP-PVDF membrane provides a barrier against water molecules in aqueous solutions, reliably preventing salt leakage outside the membrane (which could compromise (or impair) the overall selectivity (and efficiency) of the ED process). Without being bound by theory, this ion selectivity is thought to arise from the densely packed LATP particles in the surface (or skin) layer, and Li + Ions travel across the membrane matrix and toward the bottom of the membrane through LATP channels formed by densely packed LATP particles. As they approach the bottom region of the LATP-PVDF membrane, wider interparticle spaces (or gaps) between LATP particles (Figure 6h) are partially filled by PVDF polymer chains, leaving a more porous structure. When this LATP-PVDF membrane is used in an ED process, the porous structure is filled with the permeate solution, facilitating ion transport. The extent of the permeate solution and LATP channels' contribution to conductivity depends on the conductivity of the permeate solution and the conductivity of LATP (in solution). Because this process is partially carried out by LATP sedimentation and PVDF SEIPS, a network of LATP is always maintained from the skin layer to the bottom layer, and Li + Exclusive to (or Li + It forms a dedicated ion channel capable of transporting ions.

[0088] Example 3 Lithium separation performance of LATP-PVDF membrane The lithium-ion separation performance of the membrane was tested using an ED system. The ED process used in this study is a stack (or laminate) of three membranes (consisting of AEM, LATP-PVDF membrane, and AEM) in this order (AEM: anion exchange membrane). ED controls the movement of ions by the applied potential difference and has been found to be useful for brackish water desalination, water treatment, and ion recovery. In the ED experiments of the present disclosure, an LATP-PVDF membrane was used instead of a commercially available cation exchange membrane.

[0089] The ion separation performance of the LATP-PVDF membrane was investigated with various feed solutions consisting of LiCl, NaCl, MgCl2, or a combination of these three salts.

[0090]

Table 3

[0091] In single-ion permeation tests (or single-ion permeation tests) using 0.1 M LiCl, NaCl, and MgCl2 as feed solutions respectively, the concentration of Li ions on the permeate side (or permeate side or permeate side) increases with ED time. On the other hand, Na and Mg ions permeated (or penetrated) the membrane very slightly (Figure 7a). The membrane shows a Li flux of 23.35 g / (m + ·h), and the minimum fluxes of Na and Mg at the end of the ED experiment are 0.62 g / (m + ·h) and 0.35 g / (m 2+ ·h) respectively (Figure 7b). This gives an ideal selectivity of Li / Na and Li / Mg for the LATP membrane of 37.7 and 65.7 respectively (after 12 hours). 2 ·h) of Li + ions, and the minimum Na + and Mg 2+ fluxes at the end of the ED experiment are 0.62 g / (m 2 ·h) and 0.35 g / (m 2 ·h) respectively (Figure 7b). This results in an ideal selectivity of Li / Na and Li / Mg for the LATP membrane of 37.7 and 65.7 respectively (after 12 hours). + / Na + and Li + / Mg 2+ are given values of 37.7 and 65.7 respectively (after 12 hours).

[0092] Regarding the recovery of Li from various sources (or feed sources), ED experiments were conducted using LiCl solutions at various concentrations as the feed (or feedstock) to determine the practicality of the LATP-PVDF membrane (Figure 7c). As shown in Figure 7c, the Li + concentration on the permeate side (or permeate side or permeate channel) increases with both the Li + concentration of the feed solution and the operating time. This is as expected, as it can be seen that the higher the Li + concentration of the feed solution used, the greater the number of Li + ions that come into contact with the membrane surface at once. In a 0.0001 M Li + (about 4.2 ppm) feed solution, the Li + ion flux was only measured to be 0.37 g / (m + h) (Figure 7d). However, the recovery rate of Li from 300 ml of the corresponding feed solution after 12 hours was 90.4%. Thus, it has been demonstrated that the LATP-PVDF membrane can be applied to low Li 2 concentration sources. However, since the recovery of Li increases non-linearly with the concentration of the feed, it has been observed and suggested that there is an upper limit to the maximum ion flux that can be achieved by the LATP-PVDF membrane by concentrating the feed solution. This is a common step (or process) in the lithium mining industry to increase the efficiency of Li + recovery. Since the Li + concentrations from various sources can vary significantly (for example, the average Li + concentrations in seawater and brine are 170 ppb and 300 ppm, respectively), the wide application of the LATP-PVDF membrane to various feed concentrations is a great advantage for lithium separation under real-world conditions. Furthermore, in ED tests using a pure PVDF membrane instead of the LATP-PVDF membrane, the LATP channels of the LATP-PVDF membrane are Li + + concentrations can vary significantly (e.g., the average Li + concentrations in seawater and brine are 170 ppb and 300 ppm, respectively), the wide application of the LATP-PVDF membrane to various feed concentrations is a great advantage for lithium separation under real-world conditions. Furthermore, in ED tests using a pure PVDF membrane instead of the LATP-PVDF membrane, the LATP channels of the LATP-PVDF membrane are Li + ​The role of ion permeation and selectivity was investigated. When a PVDF membrane was used, the concentrations of the feed and permeate (or permeate) remained constant throughout all ED experiments. This indicates that the PVDF component of the membrane was not permeable to any ions. Furthermore, the volumes of the feed solution and permeate solution remained constant throughout all ED experiments.

[0093] Real-world applications of lithium-selective membranes require the separation of salt mixtures. In this study, salt solutions prepared with 0.1 M LiCl, 0.1 M NaCl, and 0.1 M MgCl2 were used in ED tests. As shown in Figure 7e, the Na on the permeate side (or permeate side or permeate side) + and Mg 2+ The concentration was consistently below the detection limit of the ICP-OES spectrometer (samples were sent to ALS, a third-party testing and certification company). This indicates that the LATP-PVDF film was Li + It has been confirmed that it is permeable only to ions. As a result, Li + The flux is almost halved compared to the single-ion experiment (Figure 7f). This is thought to be due to competition for ion absorption to the membrane surface. The actual ion selectivity of LATP-PVDF is determined by the permeate solution being Li + Because it contains only Li, its selectivity is significantly higher than ideal (i.e., Li + / Na + and Li + / Mg 2+ = infinity (∞). To make it easier to compare with the performance of lithium separation membranes reported so far, the Na in the permeate solution + and Mg 2+ Assuming a concentration of approximately 1 ppm, the corresponding minimum and underestimated Li + / Na + and Li + / Mg 2+ The selectivity is 134. Test results show that the LATP-PVDF membrane in this study is superior to all current Li + Li is significantly larger than that of the separation membrane. + It was shown to possess flux and selectivity.

[0094] Membrane stability To determine the strength (or robustness) of the LATP-PVDF membrane and the stability of the LATP channels, the membrane was subjected to seven cycles consisting of a 12-hour ED using a 0.1 M LiCl solution as feed and a 12-hour membrane wash with circulating DI water. Figure 8a shows that the performance of the LATP-PVDF membrane remained stable after the completion of seven cycles. In each cycle, the membrane was subjected to 24.8 to 25.7 g / m² at the end of each cycle. 2 It consistently showed the same ion flux between (h). Furthermore, the stability of the LATP-PVDF membrane was Li + This was demonstrated by performing electrodialysis at a LiCl concentration of 0.02 M until almost all of the material was recovered. A feed concentration of approximately 0.02 M (or 1000 ppm) was observed within the same experimental time as the 7-cycle stability test, Li + The material was selected so that it could permeate the membrane (Figure 8b).

[0095] No significant differences were observed in the XRD patterns or morphology (or morphology) of the LATP-PVDF membrane before and after stability testing. Based on membrane performance, crystallinity, and morphology, this membrane is considered mechanically robust and stable. Performance and energy consumption in the real world The real-world performance of LATP-PVDF membranes was demonstrated using synthetic brine solutions and seawater (see Table 3). 300 ppm Li was used as the feed solution. + (or about 0.007M Li + When a brine consisting of ) was used, similar ion-selective behavior was observed in the LATP-PVDF membrane. Here, Li + All other ions are almost completely rejected by the membrane. When using 300 ml of brine-feed solution, 65.3% Li is present within 12 hours. + Recovery can be achieved. + The ion flux is 12.23 g / (m³). 2 h) was the result of 0.01M Li +The results were similar to those of the single-ion experiment performed earlier. Based on the concentration of the permeate (detected using ICP-MS; detection limit was at the ppt level; see Methods), the concentration of Li 9107 was determined. + / Na + Selectivity was achieved. This result demonstrates that the recovery of lithium ions from brine solutions is fully feasible.

[0096] When using synthetic seawater as feed (Li + Concentration: 170 ppb), 41.8% Li in 12 hours + It was possible to recover it from synthetic seawater. Li in synthetic seawater + Because the concentration is very low, Li + The flux was quite low. Nevertheless, the actual ion selectivity was Li + / Na + Li + / K + Li + / Mg 2+ and Li + / Ca 2+ However, the values ​​were 13.0, 43.7, 46.6, and 123.6 respectively, suggesting that lithium recovery from seawater can still be achieved efficiently. However, the selectivity is significantly lower compared to when brine is used as the feed. Li in seawater feed solution + :Na + Considering that the ratio is high at 1:61765, Li + / Na + The selectivity of 13.0 is quite remarkable. + and Na + Even in the case of an equimolar mixture, such Li + / Na + No commercially available membranes can achieve this selectivity.

[0097] When synthetic seawater or brine is used as the feed solution, Li is shown by the LATP-PVDF membrane. + / Na + and Li + / K +The selectivity of the ions strongly suggests that ion separation is achieved by partial dehydration of monovalent ions. + This is especially true for feed solutions where seawater solution is dominant. In the case of lithium recovery from brine, Li + :Na + The ratio is 1:77, and Li + / Na + The selectivity was 9107, indicating that the surface (or skin) or upper (or top) layer of the membrane is sufficiently dense to prevent water leakage. This prevents undesirable ions from leaking across the membrane to the permeate side (or permeate side or permeate side).

[0098] The membrane performance data obtained from laboratory experiments and the commercially available electrodialysis system (which consists of stacked (or laminated) large-area membranes of 400 mm x 1600 mm, with a total membrane area of ​​665.6 m²) are used. 2 Using typical energy consumption data, we estimated that the real-world energy consumption on a commercial scale is approximately 1.84 kWh per kilogram of recovered lithium.

Claims

1. A membrane for separating target ions, comprising: the membrane comprises a target ion-permeable polymer-ceramic composite material; the material comprises a target ion permeable ceramic and at least one target ion permeable organic polymer, the organic polymer being bonded to the target ion permeable ceramic; A membrane that allows selective permeation of target ions, preferably lithium target ions, through said membrane.

2. The membrane of claim 1 , wherein the target ion separation membrane is a membrane for separating target ions from an aqueous solution.

3. 3. The membrane of claim 1, wherein the membrane is selectively permeable to the target ions under the influence of an electric potential.

4. 4. The membrane of claim 1, wherein the target ion permeable ceramic and the at least one organic polymer are present in the composite in a concentration (wt %) ratio (ceramic:polymer) of 1:1 to 15:1, preferably 10:

1.

5. The membrane of any one of claims 1 to 4, wherein the membrane comprises a heterogeneous dispersion of ceramic particles in a matrix formed by the polymer.

6. 6. The membrane of any one of claims 1 to 5, wherein the target ion-permeable polymer-ceramic composite has a microstructure comprising an upper layer or region of densely packed ceramic particles having reduced porosity characterized by narrower interparticle spacing, and a lower layer or region of less densely packed ceramic particles having increased porosity characterized by wider interparticle spacing.

7. The membrane of claim 6 , wherein the spaces between the particles are filled with one or more organic polymers.

8. the target ion-permeable polymer-ceramic composite comprises at least two layers; the first layer comprises a target ion permeable ceramic rich layer comprising particles of the target ion permeable ceramic; the second layer is an organic polymer rich layer; The membrane of any one of claims 1 to 7, wherein the first layer comprises more target ion permeable ceramic particles than the organic polymer rich layer.

9. The membrane of any one of claims 1 to 8, wherein the at least one organic polymer fills the interstices between the grain boundaries of the ceramic particles.

10. 10. The membrane of claim 1, wherein the target ion permeable ceramic of the target ion permeable ceramic material is compressed, and the level of compression, the density of the ceramic particles, and / or the size of the ceramic particles are not constant across a vertical cross section of the membrane.

11. 11. The membrane of claim 10, wherein the level of compression of the target ion permeable ceramic decreases across a vertical cross section of the membrane in the form of a gradient of decreasing particle compression, a gradient of decreasing particle size, and / or a gradient of decreasing particle density.

12. the target ion-permeable polymer-ceramic composite comprises at least two regions; the first region comprises a region rich in the target ion permeable ceramic, said region comprising particles of the target ion permeable ceramic packed at a higher density; 12. The membrane of any one of claims 1 to 11, wherein the second region comprises particles of the target ion permeable ceramic that are less densely packed than the first region.

13. 13. The membrane of claim 12, further comprising at least one subsequent region, said region comprising particles of the target ion permeable ceramic packed less densely than the immediately preceding region.

14. 14. The membrane according to any one of claims 1 to 13, wherein the at least one organic polymer is a hydrophilic organic polymer, preferably a fluorinated organic polymer, said organic polymer being selected from the group consisting of polyvinylidene fluoride (PVDF), sulfonated tetrafluoroethylene copolymer (Nafion), chitosan and polysulfone and combinations thereof, preferably polyvinylidene fluoride (PVDF).

15. 15. The membrane of claim 14, wherein the coating comprises two or more organic polymers, such as a combination of polyvinylidene fluoride (PVDF) and sulfonated tetrafluoroethylene copolymer (Nafion).

16. The membrane of any one of claims 1 to 15, wherein the target ion permeable ceramic is a lithium superionic conductor.

17. The lithium superionic conductor is a NASICON or LISICON material, preferably LATP(Li 1+x Al x Ti 2-x (P.O. 4 ) 3 , x=0.3 to 0.4), and most preferably Li 1.3 Al 0.3 Ti 1.7 (P.O. 4 ) 3 17. The membrane of claim 16, wherein:

18. 18. The membrane of any one of claims 1 to 17, wherein the target ion permeable polymer-ceramic composite is supported on a target ion porous support substrate, preferably a film of synthetic fabric, woven or nonwoven, a film of porous nylon, or a film of porous alumina.

19. The membrane of any one of claims 1 to 18, wherein the at least one organic polymer penetrates at least a portion of the target ion channels of the target ion permeable ceramic.

20. A membrane for separating lithium target ions from an aqueous solution of ions, the membrane comprising a lithium target ion porous support substrate supporting a lithium target ion permeable polymer-ceramic composite material; The target ion permeable polymer-ceramic composite material is Li 1.3 Al 0.3 Ti 1.7 (P.O. 4 ) 3 A membrane comprising a (LATP) ceramic bonded to polyvinylidene fluoride (PVDF), the PVDF being present in a target ion permeable polymer-ceramic composite at a concentration (wt%) ratio (ceramic:polymer) of about 10:

1.

21. A method for producing an electrodialysis membrane, comprising the following steps: preparing a solution of a target ion-permeable ceramic material (preferably LATP) and at least one organic polymer (preferably PVDF) in a volatile organic solvent, preferably dimethylformamide (DMF); solution casting the solution into a mold of a predetermined shape; evaporating the solvent to form a film of target ion-permeable polymer-ceramic composite material. A method comprising:

22. 22. The method of claim 21, wherein the step of evaporating the solvent comprises evaporation by a process of solvent evaporation induced phase separation (SEIPS) or other process that results in preferential settling of ceramic aggregates during fabrication.

23. A membrane obtainable by the method according to claim 21 or 22.

24. Use of a membrane according to any one of claims 1 to 20 or 23 in a targeted ion separation technique, preferably in a lithium ion separation technique.

25. 25. The use according to claim 24, wherein the target ion separation technique is dialysis or electrodialysis.

26. 26. Use according to claim 24 or claim 25, wherein the target ion separation technique comprises the separation of lithium ions from brine or from a lithium-containing solution derived from a lithium recycling process.

27. 24. A method of electrodialysis for the selective separation of lithium ions from brine or from a lithium-containing solution resulting from a lithium recycling process, the method comprising the step of applying a voltage to a membrane according to any one of claims 1 to 20 or 23.

28. 24. An electrodialysis stack comprising the membrane of any one of claims 1 to 21 or 23 disposed between a pair of anion exchange membranes.

29. 30. The electrodialysis stack of claim 28, comprising a plurality of membranes, each membrane disposed between a pair of anion exchange membranes.